Improving Teacher Competence Through Scientific Article Writing Training - Ivan Fachrul Marsa; Jusbaeni Jusbaeni; Taufiq Natsir; Ulmiah Muis; Andi Abidah (PT. Global Research Collaboration, 2024)
Scientific writing training was conducted at SMAN 7 Sinjai as an effort to improve the competence of educators in writing scientific articles. This activity was motivated by the low ability of teachers to conduct research and write research results in the format of articles that can be published in reputable journals. This programme was implemented for eight months using online and offline training methods, including licensing, site preparation, socialisation, training, mentoring, and evaluation. The results of the activities showed that the training participants successfully gained an understanding of scientific article writing techniques, including literature searches, the use of tools such as the Mendeley application, and writing formats according to journal standards. In addition, the teachers successfully drafted scientific articles for publication submission. This programme is expected to contribute to improving teachers' professionalism and motivate them to contribute to the development of science through scientific publications.